Experiences of Universal Health Coverage in Southeast Asia: Thailand and Indonesia - Madhurima Nundy (Social Change, 2026)
This commentary compares the universal health coverage (UHC) journeys of Thailand and Indonesia, two Southeast Asian countries that made similar political commitments to universal coverage but arrived at markedly different outcomes. Drawing on an earlier extensive review of health reforms in both countries, it traces how historical trajectories, financing choices, institutional capacity, and governance arrangements shaped each pathway. Thailand’s tax-financed Universal Coverage Scheme, launched in 2002, built on decades of investment in rural primary care and produced near-universal, pro-poor coverage with strong financial protection, despite a persistently fragmented risk pool. Indonesia’s contributory Jaminan Kesehatan Nasional scheme, launched in 2014, created a formally unified national pool but continues to struggle with an uncovered ‘missing middle,’ chronic underfunding, weak primary care orientation, and unresolved institutional conflict. The commentary argues that UHC is not a technical destination but a political settlement, continuously renegotiated, shaped by democratisation, crisis legacies, path dependence, and state capacity. It concludes with lessons for other low- and middle-income countries pursuing UHC.